Spatialtemporal Characteristics of Tunnel Traffic Accidents in China from 2001 to Present - Hao Sun; Qiuping Wang; Peng Zhang; Yujian Zhong; Xiabing Yue (Advances in Civil Engineering)
There are often greater risks in the process of tunnel construction, and because of the unpredictable tunnel features, the risks during tunnel operation are also great. Due to the substantial growth of TTAs during the recent years, the safety issues of the tunnel traffic accidents (TTAs) have become a widely discussed topic in China. This study examined 2703 TTAs that occurred in the expressway tunnels of China, from 2001 to the present. The datasets from these accidents were analyzed in detail to determine the temporal and spatial characteristics of the traffic accidents as well as the source of the traffic accident distributions in the expressway tunnels. According to the analysis results, 58% of TTAs took place in the entrance and exit zones, and the rear end accident is the most common accident. In addition, the special festivals are liable to traffic accidents, especially during the Chinese Spring Festival. In order to reduce the accidents, special traffic service needs to be taken in key periods, the expressway tunnel operation departments should improve the management rules, and all the drivers should be educated to be more careful when they enter the tunnel.